History of Christianity in Asia, Africa, and Latin America, 1450-1990: a documentary source book - Koschorke, Klaus; Ludwig, Frieder; Delgado, Mariano; Spliesgart, Roland (William B. Eerdmans Pub. Co, 2007)
The map of world Christianity has changed dramatically in just the last century. Today, the majority of Christians live in Africa, Asia, and Latin America, making Christianity a world religion as never before in history. Given that global reality, Klaus Koschorke, Frieder Ludwig, and Mariano Delgado have created the first comparative documentary history of Christianity for these regions covering the period 1450-1990. Taking the changing ecumenical conditions into account, this volume enlarges the horizon of classical church historiography. In contrast to the prevailing Western perspectives on the history of Christianity in Africa, Asia, and Latin America, voice is given here to the multitude of local initiatives, specific experiences, and varieties of Christianity in very diverse cultural contexts - addressing such questions as the colonial conquest, slavery, and the demand for ecclesiastical independence.